Novel insights into higher capacity from the Li-ion battery cathode material Li2FeSiO4. (1st January 2017) - Liivat, Anti; Thomas, Josh; Guo, Jianghuai; Yang, Yong
Abstract: A highly reactive composite cathode material incorporating nano-particles of the popular Li-ion battery cathode material Li2 FeSiO4 (LFS) is here studied to probe the activation of the controversial Fe 3+ /Fe 4+ redox couple in exploiting the second Li-ion in the formula unit – for use in rechargeable Li-ion batteries. A novel form of in situ Mössbauer spectroscopy is used to monitor the oxidation state of the Fe-ions in symmetric LFS || LFS cells. This is based on mapping the poorly resolvable Mössbauer spectra from the expected Fe 3+ /Fe 4+ redox couple in the working electrode onto the highly resolvable Fe 2+ /Fe 3+ spectra from the counter electrode. Comparison of such data from half-delithiated Li(1)Fe 3+ SiO4 || Li(1)Fe 3+ SiO4 and almost lithium-free "Li(0)Fe 4+ SiO4 || Li(0)Fe 4+ SiO4 " symmetric cells is demonstrated – to distinguish the electrode reactions from the those involving the electrolyte. Lithium is shown to cycle reversibly in the symmetric cells. However, a large proportion of the cycled lithium (∼70%) does not derive from the bulk of the electrodes, but is rather a result of high-V electrolyte degradation, where charge balance is maintained by leaching lithium from the electrolyte and inserting it into the electrodes.